Maximizing achievement in sport organizations: A multi-style leadership approach - Schneider, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In consideration of adopting an approach to sport leadership that supports Andrew`s (2009) recommendation of altering leadership behavior to meet the requirements of the organization and its members, this presentation will offer insights as to how sport leaders might effectively utilize various components of multiple leadership styles to maximize organizational efficiency. Varying forms of influence are at the disposal of the leader when dealing with the complexities and dynamic nature of organizations (Bolden, Petrov, & Gosling, 2008). The achievement of maximum outcomes from sport organization members calls for a multi-style approach to leadership. Successful leadership of sport organizations can and does take place in many forms. A multi-style approach to leadership incorporates components of all leadership styles as needed to achieve maximum organizational efficiency. Adopting a multi-style approach to sport leadership requires an understanding of the various approaches to leadership and the ability to implement specific components of leadership theories that are germane to varying objectives, circumstances, and missions of sport organizations. The extent to which sport leaders can identify and apply appropriate components of different leadership theories will help elevate the success of the organization. In the interest of effective leadership, Simplicio (2011) explored the benefits and detriments of incorporating specific leadership styles into one`s management approach. Adopting selected components of various leadership styles also requires the ability of sport leaders to periodically assume a leadership style that may not be a natural "fit" with their personality traits. To that end, this presentation will also provide a structure, including examples, that supports the sport leader`s utilization of various components of leadership theories when leading a sport organization.